Private Activity in Water and Sewerage Declines for Second Consecutive Year - Izaguirre, Ada Karina; Perard, Edouard (World Bank, Washington, DC, 2012)
In 2009 seven low- or middle-income countries implemented 35 water projects with private participation involving investment of almost US$2 billion, according to just-released data from the Private Participation in Infrastructure (PPI) database. The number of new projects with private participation that reached financial or contractual closure in 2009 declined by 46 percent compared with 2008. Annual investment commitments fell by 31 percent compared with 2008.